2014
DOI: 10.4103/0970-1591.127856
|View full text |Cite
|
Sign up to set email alerts
|

Management of the complications of BPH/BOO

Abstract: Most men will develop histological BPH if they live long enough. Approximately, half will develop benign prostatic enlargement (BPE) and about half of these will get BOO with high bladder pressures and low flow, this in turn leads to detrusor wall hypertrophy. Many of these men will only have lower urinary tract symptoms (LUTS) but a significant number will also suffer the other complications of BPH. These include urinary retention (acute and chronic), haematuria, urinary tract infection, bladder stones, bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
6
26
0
Order By: Relevance
“…Another cause for urolithiasis in men is hyperuricosuria, which leads to acid urine and favours the formation of uric acid stones such as calcium oxalate stones . In humans, a chronic urinary infection has been described as a risk factor for the formation of urinary stones . Although this was not observed in our case, there was no information about former urinary infections.…”
Section: Resultsmentioning
confidence: 53%
“…Another cause for urolithiasis in men is hyperuricosuria, which leads to acid urine and favours the formation of uric acid stones such as calcium oxalate stones . In humans, a chronic urinary infection has been described as a risk factor for the formation of urinary stones . Although this was not observed in our case, there was no information about former urinary infections.…”
Section: Resultsmentioning
confidence: 53%
“…In high-pressure chronic retention, there is bladder outflow obstruction and high voiding detrusor pressure with a poor flow rate, leading to persistently high pressure within bladder; this causes retrograde pressure and bilateral hydronephrosis (22). The increased intravesical pressure further causes detrusor hypertrophy with connective tissue collagen impregnation, leading to a hypertrophied and trabeculated bladder (23).…”
Section: Resultsmentioning
confidence: 99%
“…The histopathological report confirmed chronic pyelonephritis involving both kidneys with a hypertrophied, trabeculated bladder and attenuation of the epithelium. Speakman et al (22) have observed that the most common pathophysiological findings in men with obstructive nephropathy is chronic interstitial pyelonephritis.…”
Section: Resultsmentioning
confidence: 99%
“…It affects over 50% of men by the age of 50 and above and its prevalence increases further with the advancing age (Lim, 2017). It results from a non-cancerous enlargement of the prostate gland that is accompanied by multiple complications, including the lower urinary tract symptoms (LUTS), i.e., frequency, urgency, hesitancy, intermittency, and weak stream (Speakman and Cheng, 2014). The other risk factors, both modifiable and non-modifiable, that augment the risk of development as well as progression of BPH, besides others, include racial and genetic predisposition (Chughtai et al, 2016;Parsons, 2007).…”
Section: Introductionmentioning
confidence: 99%